2021
DOI: 10.1371/journal.pntd.0009890
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of soil transmitted helminth infections in minority indigenous populations of South-East Asia and the Western Pacific Region: A systematic review and meta-analysis

Abstract: Introduction Soil transmitted helminth (STH) infections cause one of the most prevalent diseases in man. STHs disproportionately impact socio-economically disadvantaged communities including minority indigenous populations. This systematic review aimed to quantify the prevalence of STH infection within minority indigenous populations of the South-East Asia and Western Pacific Regions. Methods The systematic review was conducted in accordance with The Preferred Reporting Items for Systematic Reviews and Meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…stercoralis in indigenous populations and their correspondent assistance healthcare professionals with unknown seroprevalence. Indigenous populations are considered one of the most exposed populations to soil-transmitted helminths due to poverty and lack of sanitary conditions [ 35 , 36 ], particularly strongyloidiasis [ 37 ]. Brazilian indigenous populations were investigated for seroprevalence and associated risk factors, and we found a relatively high prevalence of strongyloidiasis (37.6%; 174/463; CI 95%: 33.3–42.1) using an ELISA test for anti-IgG against S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…stercoralis in indigenous populations and their correspondent assistance healthcare professionals with unknown seroprevalence. Indigenous populations are considered one of the most exposed populations to soil-transmitted helminths due to poverty and lack of sanitary conditions [ 35 , 36 ], particularly strongyloidiasis [ 37 ]. Brazilian indigenous populations were investigated for seroprevalence and associated risk factors, and we found a relatively high prevalence of strongyloidiasis (37.6%; 174/463; CI 95%: 33.3–42.1) using an ELISA test for anti-IgG against S .…”
Section: Discussionmentioning
confidence: 99%
“…stercoralis methods for detecting infection, with different sensitivities and specificities, resulting in a plausible prevalence underestimation [ 41 ]. Other metanalytic study has included 20 articles on strongyloidiasis prevalence of minority indigenous populations of South-East Asia and the Western Pacific Region, revealing an overall 16.8% of serological prevalence, significantly higher (p = 0.004) than 4.1% observed by microscopy [ 36 ]. Although the ELISA test has shown different diagnostic values (75.4–91.2% and 94.8–100%, sensitivity and specificity, respectively) depending on the assay [ 38 ], the in-house ELISA test for S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important finding in the risk factor analysis was the increased odds of infection with N. americanus associated with belonging to an ethnic minority group (Gia-rai, Hmong, Xo-dang, Êđê, Dao, Mnông, Nùng, Tày and other) compared to children from the ethnic majority group in Vietnam (Kinh), while some ethnic minorities (Gia-rai, Hmong, Xo-dang and Ede) were also associated with increased odds of moderate-to-heavy-intensity N. americanus infection. The burden of STH has been shown to be high amongst indigenous ethnic minority groups throughout the Western Pacific and neighbouring South-East Asia region, namely in the Philippines and Malaysia [ 4 , 55 , 56 ]. There has been one previous study comparing the prevalence of STH between ethnic groups in Vietnam, which found high prevalence in both Kinh and ethnic minority groups [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…STHs are parasitic intestinal worms, and include hookworms ( Necator americanus , Ancylostoma duodenale and Ancylostoma ceylanicum) , Ascaris lumbricoides , Trichuris trichiura and Strongyloides stercoralis [ 2 , 3 ]. Like other NTDs, they disproportionately affect poorer, rural and indigenous communities in tropical and subtropical regions of the world [ 2 , 4 ]. High-intensity STH infections are associated with considerable morbidity including malnutrition, anaemia and impaired physical and cognitive development [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%